2017
DOI: 10.22551/2017.17.0404.10114
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric pancreatic Burkitt lymphoma with obstructive jaundice: case report of a six-year-old child

Abstract: Introduction: Burkitt lymphoma represents about 50% of non-Hodgkin lymphomas and 3% of cancers in children. It commonly affects the abdomen; however, pancreatitis is a very rare initial presentation. Less than 10 cases with this presentation are reported in the literature. Observation: We report the case of a six-year-old girl who presented a rapidly progressing obstructive jaundice evolving for a week. The LDH rate was not increased. Medical imaging has shown a global increase in the size of the pancreas, hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…The literature reports less than 10 cases of pancreatic lymphoma manifesting as acute pancreatitis at debut. Athmani et al [ 28 ] report the case of a 6-year-old female with a rapidly progressive jaundice; in that case, abdominal imaging showed an important increase in the pancreatic size, homogeneous hepatomegaly and intra- and extrahepatic biliary ducts’ dilatation. Ultimately, the histopathological examination set the diagnosis of Burkitt’s lymphoma.…”
Section: Pancreatic Malignant Tumors In Childrenmentioning
confidence: 99%
“…The literature reports less than 10 cases of pancreatic lymphoma manifesting as acute pancreatitis at debut. Athmani et al [ 28 ] report the case of a 6-year-old female with a rapidly progressive jaundice; in that case, abdominal imaging showed an important increase in the pancreatic size, homogeneous hepatomegaly and intra- and extrahepatic biliary ducts’ dilatation. Ultimately, the histopathological examination set the diagnosis of Burkitt’s lymphoma.…”
Section: Pancreatic Malignant Tumors In Childrenmentioning
confidence: 99%
“…In a recent case report and literature review by Lee et al on BL presenting as acute pancreatitis, a total of 15 cases were identified [2,[10][11][12][13][14][15][16][17][18][19][20][21]. Twelve of the 15 cases were children [2,[10][11][12][13][14][15][16][17][18], 5/15 presented with jaundice [2,10,11,15,17], and 10/15 had diffuse pancreatic enlargement [2, 10, 11, 13-18, 20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent case report and literature review by Lee et al on BL presenting as acute pancreatitis, a total of 15 cases were identified [2,[10][11][12][13][14][15][16][17][18][19][20][21]. Twelve of the 15 cases were children [2,[10][11][12][13][14][15][16][17][18], 5/15 presented with jaundice [2,10,11,15,17], and 10/15 had diffuse pancreatic enlargement [2, 10, 11, 13-18, 20, 21]. Only 1/12 reported CBD dilation up to 9 mm on MRI, significantly less than the 26 mm dilation seen in our patient on MRCP [2].…”
Section: Discussionmentioning
confidence: 99%
“…O Vírus da Imunodeficiência Humana (HIV), particularmente, propicia patógenos de infecções oportunistas, incluindo o Vírus Epstein-Barr (EBV) (BACCHI et al, 1996).…”
Section: Introductionunclassified
“…No Brasil, onde há alta incidência de co-infecção HIV e EBV, um estudo encontrou relação de 55% entre a presença de EBV e o desenvolvimento de LNHs nos pacientes com SIDA (LIMA et al, 2006). Do total de casos, 25% foram caracterizados como células pequenas não clivadas, do tipo Burkitt (BACCHI et al, 1996).…”
Section: Introductionunclassified